Analisis Rasio Keuangan Perusahaan Telekomunikasi yang Terdaftar di Bursa Efek Indonesia (BEI) pada Tahun 2016–2020 - Meta Analia Anggraini; Titi Rapini; Riawan Riawan (Goodwood Akuntansi dan Auditing Reviu, 2023)
In today’s modern era, the development of telecommunications in Indonesia is experiencing very rapid development. For the development of the telecommunications industry in Indonesia, technology has a very vital role. This is because the development of telecommunications always follows the existing technology. Purpose: This examine goals to determine the monetary performance of telecommunications corporations in Indonesia, namely PT. Telekomunikasi Indonesia Tbk, PT. Indosat Tbk, PT. XL Axiata Tbk, PT. Smartfren Telecom Tbk in 2016 – 2020 in terms of 4 financial ratios, specifically liquidity, solvency, activity, and profitability. Methodology: Data analysis in this study uses data from the financial reports of four telecommunications companies listed on the Indonesia Stock Exchange. The research method uses by researchers is a descriptive quantitative methode. Results: The results of this study have a look 1) Liquidity ratio evaluation the use of the fast ratio indicates that the 4 telecommunications organizations are in destructive situation, 2) Solvability evaluation the use of the debt to asset ratio indicates that the economic overall performance of the four businesses is in adverse circumstance, 3) activity ratio analysis using overall asset turnover suggests the overall performance of the four organizations in adverse circumstance, 4) Profitability ratio evaluation the use of return on funding suggests that the 4 businesses have bad financial overall performance.